Four unruly women: stories of incarceration and resistance from Canada's most notorious prison - McCoy, Ted (UBC Press, 2019)
"Bridget Donnelly. Charlotte Reveille. Kate Slattery. Emily Boyle. Until now, these were nothing but names marked down in the admittance registers and punishment reports of Kingston Penitentiary, Canada's most notorious prison. In this shocking and heartbreaking book, Ted McCoy tell these women's stories of incarceration and resistance in poignant detail. The four women served sentences at different times over a century, but they shared experiences that illuminate how those most marginalized in society--the poor, the sick, and the disadvantaged--reckoned with poverty and crime and grappled with the constraints placed on them by shifting notions of punishment and reform. The inhumanity they suffered while locked away from male prisoners in dark basement wards--from starvation and corporal punishment to sexual abuse and neglect--stands as profoundly disturbing evidence of the hidden costs of isolation, punishment, and mass incarceration."--